Senegal - Joint World Bank-IMF Debt Sustainability Analysis - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
Senegal has expanded its debt perimeter to include para-public entities and state-owned enterprises (SOEs) and remains at low risk of debt distress despite short-term breaches of two external debt indicators under the most extreme scenarios. The low risk of debt distress is predicated on: (i) ongoing debt liability management, guarantees to address currency risk, access to liquid financial assets and a sound track record of market access; and (ii) adherence to the planned fiscal consolidation path, an acceleration of reforms, and a prudent borrowing strategy. Looking ahead, it will be important to contain fiscal pressures from Treasury operations and address fiscal risks from the broader public sector, including the energy sector.